Modeling of Meteorological Parameters for United Arab Emirates - Al Sheikh, Riad Mohamed (2002)
There has been an increasing world interest in clean renewable energies (mainly solar radiation and wind energies) due to the minimal environmental problems resulting from their uses. The continuous depletion of traditional and conventional energy resources and the growing world concern about the environment have led to an extensive research and development efforts in order to improve the energy conversion efficiencies and economics of utilization solar energy devices. However, it is important to identify the potential of available energy resources on the site where renewable energy is to be utilized. Meteorological information is critical to the assessment of the energy resources available and to the performance of many different types of renewable energy systems. Potential of the renewable energy available is strongly influenced by climatic factors such as air temperature, relative humidity, sunshine duration and natural energy supply. Solar radiation is strongly weather dependent. In the United Arab Emirates weather conditions are monitored by meteorological stations across the country and weather data are collected by various meteorological agencies.